Alleged case of blasphemy on podcast: Forensic linguistic analysis - Susilowati, Novi Eka; Arimi, Sailal; Surahmat, Surahmat; Imamah, Fardan Mahmudatul (citeus, 2023)
This study aimed to analyze the linguistic features that allegedly contained elements of blasphemy in Jenderal Dudung Abdurrachman's (JDA) speech. The analysis was carried out using a forensic linguistic perspective. This research data is in the form of JDA utterances delivered in a broadcast conducted with Deddy Corbuzier (DC). Based on a forensic linguistic analysis of the text of JDA's conversation with DC on Deddy Corbuzier's podcast, it can be concluded that JDA's linguistic evidence does not support blasphemy but a lack of knowledge in religion, especially in matters of faith. Due to the lack of knowledge of religion, JDA interprets religion and personifies God according to his understanding. In JDA's speech, there is also no intention to tarnish religion because the controversial JDA's speech cannot be interpreted partially but can be interpreted with other speeches. If it is related to other utterances, it can be concluded that there is no intention of JDA to tarnish religion. However, there are efforts by JDA to invite audiences to follow JDA's understanding and interpretation of religion.